Development of An Air Quality Model For Public Health Risk Analysis (Case Study of Dangku Village Special Coal Terminal, Muara Enim, South Sumatra) - Tri Riska Putri; Khoe Susanto Kusumahadi; Retno Widowati; Yeremiah Rubin Camin (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
Mining for coal is a human activity that can contribute to air pollution. Solar power generation using a generator to produce electricity is one of the activities that cause air pollution. Electricity is crucial for mining operations, particularly in terminals that transport coal by river or sea. This study aims to develop a model of air pollution caused by PT XYZ's solar generator in Dangku Village, Muara Enim, South Sumatra, in the form of patterns of distribution and concentration levels of NO2 and CO pollutants, as well as to assess the health risks to the local community. The modelling development method employs the AERMOD software by inputting air quality data, meteorology, the specifications of the existing 2-meter chimney, and topography. To achieve NO2 levels of 180 ug/m3 and CO levels of 18.2 ug/m3, the model results indicate that the chimney's height must be increased to 4 metres in order to meet the quality standard for NO2 and CO levels. Regarding the results of the analysis of the level of public health risk in the area, there is no significant difference between chimneys measuring 2 and 4 metres. Abstrak: Penambangan batu bara merupakan kegiatan manusia yang dapat berkontribusi terhadap pencemaran udara. Pembangkit listrik tenaga surya dengan menggunakan genset untuk menghasilkan listrik merupakan salah satu kegiatan yang menimbulkan pencemaran udara. Listrik sangat penting untuk operasi pertambangan, terutama di terminal yang mengangkut batubara melalui sungai atau laut. Penelitian ini bertujuan untuk mengembangkan model pencemaran udara akibat pembangkit tenaga surya PT XYZ di Desa Dangku, Muara Enim, Sumatera Selatan, berupa pola sebaran dan tingkat konsentrasi polutan NO2 dan CO, serta mengkaji risiko kesehatannya. kepada masyarakat setempat. Metode pengembangan pemodelan menggunakan perangkat lunak AERMOD dengan memasukkan data kualitas udara, meteorologi, spesifikasi cerobong 2 meter eksisting, dan topografi. Untuk mencapai kadar NO2 sebesar 180 ug/m3 dan kadar CO sebesar 18,2 ug/m3, hasil model menunjukkan bahwa tinggi cerobong asap harus ditambah menjadi 4 meter agar memenuhi baku mutu kadar NO2 dan CO. Terkait hasil analisis tingkat risiko kesehatan masyarakat di wilayah tersebut, tidak ada perbedaan yang signifikan antara cerobong berukuran 2 dan 4 meter.